Community-Engaged Approaches to Cervical Cancer Prevention and Control in Sub-Saharan Africa: A Scoping Review - Habila, Magdiel A.; Kimaru, Linda Jepkoech; Mantina, Namoonga; Valencia, Dora Yesenia; McClelland, D. Jean; Musa, Jonah; Madhivanan, Purnima; Sagay, Atiene; Jacobs, Elizabeth T. (Frontiers in Global Women's Health, 2021)
Background: Cervical cancer remains one of the top causes of cancer mortality among African women. Cervical cancer screening and early detection and treatment of precancer is one of the evidence-based interventions to reduce incidence and mortality. The application of community-based participatory research (CBPR) has been used in the United States to improve participation in screening and reduce cervical cancer disparities. However, it is unclear whether these engaged approaches have been used in sub-Saharan African to address disparities related to cervical cancer mortality. Objectives: Highlight community engagement in cervical cancer prevention and control in Sub-Saharan Africa (SSA), describe the community engagement efforts that are currently being used, and to describe the best practices for community engagement toward the end-goal of cervical cancer prevention and control. Methods: We searched PubMed, Embase, CINHAL, African Journals Online (AJOL), and African Index Medicus-WHO from inception until June 8, 2020. After screening 620 titles and abstracts, and reviewing 56 full-text articles according to inclusion and exclusion criteria, 9 articles met the selection criteria and were included. Relevant data variables were extracted from the included articles and a narrative synthesis was performed. Results: Between 2005 and 2019, 9 articles describing research in Ghana, Kenya, Zambia, Senegal, South Africa, and Nigeria were included. These articles described work that largely took place in rural settings predominantly among women age 15–65 years. Leveraging community networks such as community health workers, religious organizations, traditional leaders, and educational institutions increased awareness of cervical cancer. Working within existing social structures and training community members through the research effort were promising methods for addressing the disparities in cervical cancer incidence and mortality among communities. Discussion: The findings of this scoping review have contributed to the understanding of which novel approaches to community-based practices can be used to address cervical cancer disparities among SSA communities that carry a disproportionate disease burden. Community engagement in the research process, while effortful, has shown to be beneficial to researchers and to the communities that they serve, and provides valuable next steps in the effort to address cervical cancer disparities in SSA.